Changing the view on spastic movement disorder management to improve active movement competence in the upper motor neuron syndrome: a clinical perspective - Jörg Wissel; Jorge Hernandez Franco (Frontiers in Neurology)
It is common in clinical practice to evaluate active movement in spastic movement disorders (SMDs) associated with the upper motor neuron syndrome in terms of resistance to passive movement in the rest position, with the assumption that this may reflect motor control when the patient is in active motion. In addition, the definition of spasticity as a velocity-dependent resistance to passive movement does not account for the impact of abnormal muscle synergies (synkinesia), on active motion of upper and lower limbs in SMDs. In this article, we put forward our theory that synkinetic movement patterns are controlled by activation from spinal afferents and inhibition from the cortex, and become disturbed following a loss of inhibition and change to spinal afferents following damage to the corticospinal tract. In this regard, we propose a change in the focus from passive to active function at the evaluation stage of the SMD management plan, and a new treatment approach to modulate muscle synergies with botulinum neurotoxin type A therapy.